Perbandingan Hukum Waris Islam dan Hukum Waris Perdata di Indonesia - Ilmayati Ilmayati; Sukaesih Sukaesih; Jannatunnaim Jannatunnaim (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Inheritance Law is an integral part of the legal system that governs the transfer of a person's assets after death to their heirs. In Indonesia, there are two dominant systems of inheritance law: Islamic Inheritance Law and Civil Inheritance Law (Burgelijk Wetboek). These two systems differ in terms of their philosophical foundations, norms, and methods of distribution. Islamic Inheritance Law is rooted in Sharia, based on the Qur’an, Hadith, Ijma', and Qiyas, emphasizing principles of distributive justice, social responsibility, and family blessings. On the other hand, Civil Inheritance Law is derived from the continental European legal system, upholding the principle of testamentary freedom and the prioritization of equal rights among heirs. A comparison between the two reveals significant differences in the structure of heirs, the size of inheritance portions, and the possibility of making a will. For instance, in Islamic Inheritance Law, the inheritance rights of men and women differ due to considerations of financial responsibility, while in Civil Law, inheritance distribution is more egalitarian, without gender distinction. This study employs a normative-comparative approach by examining laws, legal codes, and religious fatwas as the basis for comparison. The objective of this research is to understand how both systems are implemented within Indonesia’s multicultural society and to analyze their legal implications for inheritance justice. The findings indicate that these differing systems often lead to conflicts, especially in families with members of diverse legal or religious backgrounds. Therefore, it is crucial for policymakers and legal practitioners to promote harmonization and provide legal clarity that ensures certainty and justice for all parties in inheritance matters.